Combination Effect of Solid Waste of Gracilaria Extraction and Sargassum Powder on Nitrogen Content of Bio Fertilizer. Issue 1 (March 2021) - Basmal, J; Kusumawati, R; Rahman, N; Hanafia, Z
Abstract: The solid waste of Gracilaria extraction contains agar, while Sargassum contains alginate. Both contain cellulose, hemicellulose, lignin, celite, micro and macronutrients, and plant growth promoters. In this research, the two ingredients were formulated to produce biofertilizers. The treatment given was a combination of solid waste of Gracilaria extraction (39, 48, 56, and 68%) with Sargassum flour (29, 20, 12, and 0%), while other organic matter became a fixed variable. The research aims to get the best combination of solid waste of Gracilaria extraction and Sargassum flour which produces the highest N content. The results showed that the best combination to produce the highest N content was LIA1 (39% solid waste of agar extraction and 29% Sargassum flour). However, LIA3 treatment (56% solid waste of agar extraction and 12% Sargassum flour) closed to the technical requirements of solid organic fertilizer. The characteristics of LIA3 fertilizer are 0.75% N content, 47.08% moisture content, 8.80 acidity degree, 6.85x10 9 cfu/g total bacteria and 41.95x10 4 cfu/g total mold.